Managing Religious Diversity in a Multi-Faith Society: Indian Constitutional Practices and Islamic Models of Plural Coexistence - Kumar, Sajad Ahmad (PT. Riset Press International, 2026)
This research paper explores the convergence between the Indian constitutional framework and classical Islamic models of pluralism, specifically the Charter of Madinah (Mithaq al-Madinah). Amidst rising global and domestic communal tensions, the study examines how India’s principled distance secularism aligns with the Islamic concept of a Covenantal State (Dar-ul-Ahd). Utilizing a qualitative comparative methodology, the paper analyzes Articles 14, 15, and 25–30 of the Indian Constitution alongside Quranic mandates for mutual recognition (Lita’arafu) and historical Prophetic precedents. The findings suggest that Islamic political theology offers a robust, faith-led justification for democratic citizenship and minority rights, transcending mere tolerance in favour of active pluralism. By bridging the gap between constitutional morality and religious ethics, the study provides a normative framework for social cohesion in multi-faith societies. It concludes that the Indian Constitution serves as a contemporary social contract that fulfils the pluralistic spirit of early Islamic governance models.